A Systematic Review : The Effects Of Pilates Exercise On Sleep Quality In Postpartum Women: Sistematik Review : Pengaruh Pilates Terhadap Kualitas Tidur Pada Ibu Nifas - Argaheni, Niken Bayu (Jurnal Kebidanan Midwiferia, 2021)
Background: Poor sleep quality is associated with old age among the general population, but only a few studies have focused on postpartum women. Poor quality sleep for a long time can reduce a woman's ability to carry out maternal and family duties after childbirth. This study aimed to investigate the effect of Pilates on sleep quality in postpartum women. Method: Systematic review using the database: Google Scholar. The search results that meet the criteria are then analyzed for articles. Results: Pilates exercise was shown to significantly improve sleep quality in postpartum mothers. Conclusion: Therefore, Pilates exercises can be used as an exercise routine for postpartum mothers to improve physical and mental health during the postpartum period.